2014
DOI: 10.1007/s00345-014-1339-9
|View full text |Cite
|
Sign up to set email alerts
|

Common trend: move to enucleation—Is there a case for GreenLight enucleation? Development and description of the technique

Abstract: BackgroundTransurethral laser prostatectomy has evolved as a viable alternative for the management of benign prostate enlargement. Since the renaissance of laser prostatectomy with the advent of the holmium:yttrium–aluminum–garnet laser in the 1990s, various lasers and subsequent procedures have been introduced. These techniques can be categorized as vaporizing, resecting, and enucleating approaches. Photoselective vaporization of the prostate (PVP) is dominated by high-power lithium triborate (LBO) crystal la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 22 publications
1
45
0
1
Order By: Relevance
“…In addition, it should be emphasized that the concept of anatomical enucleation being a widely energy-free technique can be performed with any kind of energy for hemostasis and not only thulium laser. Accordingly, variations of anatomical transurethral enucleation have been developed with other energy sources such as GreenLight laser (GreenLEP) [13]. Still, thulium laser appears as an excellent energy source for retrograde anatomical enucleation of the prostate as it offers a clear and bloodless incision through prostatic tissue necessary in the initial steps of the operation when incision at 5 and 7 o'clock of bladder neck is performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be emphasized that the concept of anatomical enucleation being a widely energy-free technique can be performed with any kind of energy for hemostasis and not only thulium laser. Accordingly, variations of anatomical transurethral enucleation have been developed with other energy sources such as GreenLight laser (GreenLEP) [13]. Still, thulium laser appears as an excellent energy source for retrograde anatomical enucleation of the prostate as it offers a clear and bloodless incision through prostatic tissue necessary in the initial steps of the operation when incision at 5 and 7 o'clock of bladder neck is performed.…”
Section: Discussionmentioning
confidence: 99%
“…ThuVEP focuses on the favorable vaporization effect of continuous-wave lasers to perform a fast, effective and safe enucleation, whereas ThuLEP focuses on almost blunt mechanical enucleation using the laser only for dissection of adherences and mucosa. The latter on anatomy focusing approach was mimicked by other continuous-wave lasers (LBO/"Greenlight" and 980 nm diode laser) that had not been found suitable for enucleation at the initial point of the discussion [5,6].…”
mentioning
confidence: 99%
“…followed in 2004 [2], then later in the end of the 2000s all other transurethral laser-based enucleation techniques: Tm:YAG Vapoenucleation (ThuVEP) [3], transurethral anatomical enucleation with Tm:YAG Support (ThuLEP) [4], diode laser enucleation of the prostate (DiLEP) [5] and finally Lithium-Borate "Greenlight" enucleation of the prostate (GreenLEP) [6] appeared on the market to finally replace open prostatectomy (OP) and TURP. It took Thulium:YAG as the challenger to initiate a discussion about the impact of laser in transurethral enucleation.…”
mentioning
confidence: 99%
“…Kuntz et al demonstrated equivalent functional outcomes between HoLEP and open simple prostatectomy with 5-year follow-up for prostates over 100 grams [39]. A novel enucleation technique was recently reported by Gomez et al that utilizes the Greenlight laser [40]. However, enucleation techniques are not as commonly performed as other minimally invasive procedures, possibly due to a longer learning curve [41,42] and the requirement of a tissue morcellator to remove the large volume of adenoma.…”
Section: Variables and Patient Characteristics That May Influence Thementioning
confidence: 95%